2016
DOI: 10.2217/fmb-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Staphylococcus Argenteus in Eastern China based on a Nonribosomal Peptide Synthetase ( NRPS ) Gene

Abstract: The PCR-based method targeting the NRPS gene can simultaneously identify and distinguish S. argenteus and S. aureus. All representative sequences of rpoB generated in this study were deposited in GenBank under accession numbers SJTU F20002, KT767581; SJTU F20269, KT767582; SJTU F20419, KT767583; SJTU F20420, KT767584; SJTU F20124, KT767585; SJTU F21164, KT767586; SJTU F21285, KT767587; SJTU F21224, KT767588; SJTU F21155, KT767589; SJTU F21294, KT767590; SJTU F20030, KT767591; SJTU F20044, KT767592; SJTU F20135… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 37 publications
5
74
0
Order By: Relevance
“…The NRPS gene has been identified in studies of a diverse array of related S. aureus and S. argenteus . This study found that NRPS amplification can differentiate S. argenteus from S. aureus , as also reported previously (Zhang et al., ). The sequences of NRPS amplicons analyzed using the GenBank database also corresponded to the MALDI‐TOF MS results.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The NRPS gene has been identified in studies of a diverse array of related S. aureus and S. argenteus . This study found that NRPS amplification can differentiate S. argenteus from S. aureus , as also reported previously (Zhang et al., ). The sequences of NRPS amplicons analyzed using the GenBank database also corresponded to the MALDI‐TOF MS results.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that three isolates (U19 T10.1, U43 S18.1, and U43 S18.3) have a PCR product of approximately 340 bp, which was correlated with S. argenteus as reported by Zhang et al (2016). In contrast, the five other suspected isolates had a PCR product of nearly 160 bp, which was reported to correlate with S. aureus (Zhang et al, 2016). The sequences of NRPS amplicons were analyzed for similarity using the GenBank database, which showed that bacterial isolate no.…”
Section: Nrps Gene Amplification Of S Argenteussupporting
confidence: 62%
See 3 more Smart Citations